Answer:
B.
![y = (2)/(3) x + 5](https://img.qammunity.org/2021/formulas/mathematics/high-school/ey6tjqddq43oztxevpgab6dbaesopjn1ns.png)
Explanation:
Let's use the slope equation first. The slope equation is as follows:
![(y2-y1)/(x2-x1) = slope](https://img.qammunity.org/2021/formulas/mathematics/high-school/qgxamlr1e8vnttamgvagtcde341cpw65ub.png)
This is what is given in the equation:
Let's label each component of the equation using these points:
y2 = 9
y1 = 7
x2 = 6
x1 = 3
Now, plug these into the equation
![(9-7)/(6-3) = (2)/(3)](https://img.qammunity.org/2021/formulas/mathematics/high-school/vyl0jo5xjb9pbv7851gu9u1uv0qbck125t.png)
We can now eliminate A and C of the answer choices.
Now let's find the y intercept
Right now we have the following equation
![y = (2)/(3) x+ (y intercept)](https://img.qammunity.org/2021/formulas/mathematics/high-school/16zgxnxfuouetpzn49vful3bp6yzqngfam.png)
In order to find the y intercept we need to plug in one of the given points into the equation. Let's use point (3,7).
The equation should look like this now:
![7 = (2)/(3)(3) + (yintercept)](https://img.qammunity.org/2021/formulas/mathematics/high-school/elee1x8sccvg9jwrpnmpysmsbv4d3vffl6.png)
Now lets solve for the y-intercept
![7 = (2)/(3)(3) + (yintercept)\\7 = (6)/(3) + (yintercept)\\7 = 2 + (yintercept) \\5 = yintercept](https://img.qammunity.org/2021/formulas/mathematics/high-school/mfruex39onznd0vcaa8dqxt0z5hfu2g8w0.png)
Now that we found the y-intercept is 5 we have our full equation!
![y = (2)/(3) x + 5](https://img.qammunity.org/2021/formulas/mathematics/high-school/ey6tjqddq43oztxevpgab6dbaesopjn1ns.png)
Hope this helps!!
- Kay